The denial of death - Becker, Ernest (Free Press, 2023)
"In bold contrast to the predominant Freudian school of thought, Becker tackles the problem of the vital lie--man's refusal to acknowledge his own mortality. In doing so, he sheds new light on the nature of humanity and issues a call to life and its living that still resonates decades after its writing."--Back cover.